2019
DOI: 10.1530/ec-19-0341
|View full text |Cite
|
Sign up to set email alerts
|

Tumor induced osteomalacia in head and neck region: single center experience and systematic review

Abstract: Tumor-induced osteomalacia in the head and neck region remains a challenging diagnosis to manage. Literature pertaining to management and outcome details remains sparse. We describe two cohorts: cohort 1 included seven patients from a single center in Western India with tumors located in paranasal sinuses (n = 3), intracranial (n = 2) and maxilla (n = 2). The unique features from our series is the management of persistent disease with radiation therapy (n = 2) and peptide receptor radionuclide therapy (PRRT) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 125 publications
2
23
0
Order By: Relevance
“…These tumors are usually slow growing, benign and small. They are commonly found in the craniofacial region or in the extremities [ 4 ]. Other histological types include fibromas, chondrosarcomas, neuroblastomas, and prostate carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are usually slow growing, benign and small. They are commonly found in the craniofacial region or in the extremities [ 4 ]. Other histological types include fibromas, chondrosarcomas, neuroblastomas, and prostate carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found that about 50% of patients showed signs of tenderness and/or swelling at the proposed site of the tumor or swelling. Therefore, careful physical examination can help early detection of tumors in TIO patients (4). Tumors in jaw can lead to pathological loosening of teeth, fall off, sometimes slightly bulging jaw.…”
Section: Clinical Featurementioning
confidence: 99%
“…After tumor resection, the blood phosphorus level quickly returned to normal and the symptoms were relieved within few months. To date, less than 200 cases of osteomalacia caused by maxillofacial tumors have been reported in literature (4). There are two main reasons for the low number of reported cases: first, the prevalence of TIO is low and less cases occur in the maxillofacial region; second, clinicians are poorly aware of the relationship between osteomalacia and mesenchymal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, some patients may develop tumor recurrence and benefit from a second excision [2]. Radiotherapy has been rarely used in case of inoperable tumors or incomplete resections [3][4][5][6][7][8][9]. We report the case of a patient who had a multiple recurrent ossifying fibromyxoid tumor in the left frontal sinus causing TIO.…”
Section: Introductionmentioning
confidence: 99%